A numerical analysis investigation to optimize the performance of the Ranque–Hilsch Vortex tube by changing the internal tapering angle - Muneer Sungur; Emad Elnajjar; Mohammad O. Hamdan; Salah A.B. Al-Omari (International Journal of Thermofluids, 2023)
A vortex tube is a device that separates compressed air into two streams: one with a higher temperature (hot stream) and the other with a lower temperature (cold stream). It is a popular cooling option because it is small, safe, and affordable. The main objective of this thesis is to examine the energy separation performance of RHVT by varying the internal tapering angles of convergent angles (2°, 1.75°, 1.5°, 1.25°, 1°, 0.75°, and 0.5°), straight angles (0°), and divergent angles (0.5°, 1°, 2°, 4°, and 6°), While the cold mass fraction is constant (0.317). Length-to-diameter ratio (Lt/Dt), inlet pressure, and the cold mass fraction were investigated to achieve the highest energy separation of RHVT. This thesis conducts a numerical study on the flow structure in a vortex tube using the shear stress transport k-ω turbulence model with viscous heating. The optimal energy separation occurred at a 1.75° convergent angle, Lt/Dt ratio of 3, the inlet pressure of 600 kPa, and a cold mass fraction of 0.56. The internal flow structure of the vortex tube consists of a forced vortex, transition, and free vortex regions, as shown by the static temperature radial distribution This distribution provides an understanding of the energy separation mechanism of the vortex tube by correlating it with the density gradient along the radial direction. The simulation results were validated by experimental data obtained from the literature for the same vortex tube parameters.